059 Relationship between exercise related blood pressure response and differences in magnitude of left ventricular hypertrophy between African/Afro-Caribbean (black) athletes and Caucasian athletes. (22nd September 2015) - Gati, S; Papadakis, M; Basavarajaiah, S; Rawlins, J; Chandra, N; Sawyer, E; Carby, L; Sharma, S
Abstract : Purpose: Participation in regular physical exercise is associated with a greater magnitude of left ventricular hypertrophy in male athletes of African/Afro-Caribbean origin (black athletes) compared with athletes of Caucasian origin of similar age and size, participating in similar exercise disciplines. The precise genetic, biochemical and physiological mechanisms for these differences is unknown. However, the role of exercise related blood pressure response as a determinant of exercise induced left ventricular hypertrophy has not been investigated. Aim: The study sought to investigate whether there were differences in exercise related blood pressure response in black athletes and Caucasian athletes. Method: Between 2004 and 2007, 300 black athletes and 300 whites athletes (mean age 20±5 years) participating at regional or national level underwent echocardiographic evaluation. Of these 54 black athletes (18%) and 12 white athletes (4%) exhibited a LV wall thickness >12 mm indicating LVH. Black and Caucasian athletes with left ventricular hypertrophy of >12 mm were subject to exercise stress testing with simultaneous blood pressure recording using the Bruce protocol. All athletes were exercised to the point of volitional exhaustion. Results: Black athletes exhibited a greater mean left ventricular wall thickness compared with white athletes (11.3±1 mm; range 13–16 mm v. 10±1.5 mm; range 13–14 mm: p<0.0001). The blood pressure responses to exercise are tabulated below (Abstract 59 Table 1 ). There were no significant differences in blood pressure response to exercise between black athletes and white athletes. Conclusion: The greater magnitude of left ventricular hypertrophy in blacks is not explained by a difference in exercise related blood pressure response.